Impact of vocational education and training on employment: an empirical study in the Northern province of Sri Lanka - Sooriyakumar, K. (Elsevier, 2021)
This paper studies the impact of vocational education and training (VET) on the probability of getting job. 4562 individuals who were randomly selected for annual labor force survey were included in this study. Nearest- neighbor matching method has been chosen for this study. The result of this study shows that VET increases the probability of getting job by 17 percent. The logit model for participation in VET indicates that the probability of participating in VET by a female student is lower than that of a male student and also the probability to participating in VET increase with schooling and decrease with age. This study suggests that more students should be admitted to the VET programme and government authority should encourage and motivate school children, especially female students, to enroll in VET programme.
Keywords: Matching; Propensity Score; Treatment Effect Model; Vocational Education; Training